Freckleface Strawberry and the really big voice - Moore, Julianne (Doubleday Books for Young Readers, 2016)
After a noisy summer, Freckleface Strawberry and her friends return to school where the only time they should be loud is at recess, but Windy Pants Patrick cannot remember to use his indoor voice, and that comes in handy before the day is through.